2021
DOI: 10.1038/s41420-021-00674-y
|View full text |Cite
|
Sign up to set email alerts
|

m6A reader IGF2BP2-stabilized CASC9 accelerates glioblastoma aerobic glycolysis by enhancing HK2 mRNA stability

Abstract: N6-methyladenosine (m6A) has been identified to exert critical roles in human cancer; however, the regulation of m6A modification on glioblastoma multiforme (GBM) and long non-coding RNA (lncRNA) CASC9 (cancer susceptibility 9) is still unclear. Firstly, MeRIP-Seq revealed the m6A profile in the GBM. Moreover, the m6A-related lncRNA CASC9 expression was significantly elevated in the GBM tissue and its ectopic high expression was associated with poor survival, acting as an independent prognostic factor for GBM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…A study on GBM found that by activating the IGF2BP2/PI3K/Akt axis, IGF2BP2 can significantly promote cell proliferation, migration, invasion, and EMT ( 30 ). Additionally, long noncoding RNA (LncRNA) CASC9 and IGF2BP2 synergistically increases the stability of HK2 mRNA, thereby promoting aerobic glycolysis in GBM ( 31 ). Similarly, IGF2BP2 stabilizes the HK2 and SLC2A1 mRNAs, and accelerates glycolytic metabolism and cell proliferation in colorectal cancer ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on GBM found that by activating the IGF2BP2/PI3K/Akt axis, IGF2BP2 can significantly promote cell proliferation, migration, invasion, and EMT ( 30 ). Additionally, long noncoding RNA (LncRNA) CASC9 and IGF2BP2 synergistically increases the stability of HK2 mRNA, thereby promoting aerobic glycolysis in GBM ( 31 ). Similarly, IGF2BP2 stabilizes the HK2 and SLC2A1 mRNAs, and accelerates glycolytic metabolism and cell proliferation in colorectal cancer ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, lncRNA PCAT6 interacts with IGF2BP2 to promote bone metastasis by stabilizing insulin-like growth factor1 receptor (IGF1R) mRNA 153 . In glioblastoma, IGF2BP2 recognizes the m 6 A site of lncRNA CASC9 and increases its stability, and CASC9 cooperates with IGF2BP2 to form a complex that stabilizes hexokinase 2 (HK2), promoting aerobic glycolysis 154 . In pancreatic cancer patients, IGF2BP2 is associated with poorer prognosis, and mechanistically, IGF2BP2 plays as m 6 A reader for modification of lncRNA DANCR and stabilizes its mRNA 155 .…”
Section: The Role Of Igf2bps As M 6 a Reader In Ca...mentioning
confidence: 99%
“…Insulin-like growth factor 2 mRNA-binding protein (IGF2BP1/2/3, also known as IMP1/2/3) belongs to the K homology domain family and is one of the M 6 A readers involved in the occurrence and development of cancers by interacting with different RNAs (50,51). lncRNA CASC9 has a M 6 A site in glioblastoma multiforme (GBM), which is recognized by IGF2BP2 and enhances the stability of CASC9 (52).…”
Section: Lncrnas Interact With Rbps To Regulate the Reprogramming Of ...mentioning
confidence: 99%
“…Insulin-like growth factor 2 mRNA-binding protein (IGF2BP1/2/3, also known as IMP1/2/3) belongs to the K homology domain family and is one of the M 6 A readers involved in the occurrence and development of cancers by interacting with different RNAs ( 50 , 51 ). lncRNA CASC9 has a M 6 A site in glioblastoma multiforme (GBM), which is recognized by IGF2BP2 and enhances the stability of CASC9 ( 52 ). CASC9 interacts with IGF2BP2 to form an IGF2BP2/CASC9 complex, which can bind to the M 6 A modification site of HK2, promote the expression of HK2 by improving the stability of HK2 mRNA, and ultimately promote the Warburg effect ( 52 ).…”
Section: Lncrnas Interact With Rbps To Regulate the Reprogramming Of ...mentioning
confidence: 99%